Pandemia e educação na escola pública: um relato possível e incompleto (Revista NUPEART, 2020)
My first steps as educator were taken while the world was experiencing the first pandemic of the 21st century and inserted in the realm of a nacional political and health crisis. Right on the spot, we were obliged to shift from face-to-face to virtual reality.While teaching at a Public School, I had no room to think or create new ways beyond the rigid and old established guidelines. But with the strike of the pandemic, these guidelines became useless and our school was begging for new ideas.This disease allowed me, for the first time, to enjoy some freedom to experiment. In this work, I will expose this unpredicted reality, from the point of view of an Art and Theater teacher, and try to underline its consequences to a small public school in Florianópolis.